Występowanie Erysiphe alphitoides w drzewostanach dębowych dotkniętych klęską powodzi - Szewczyk, Wojciech; Baranowska-Wasilewska, Marlena; Behnke-Borowczyk, Jolanta; Kuźmiński, Robert; Kwaśna, Hanna; Mańka, Małgorzata; Łakomy, Piotr (Leśne Prace Badawcze, 2016)
Pedunculate oak ( Quercus robur L.) is the most valuable deciduous tree species in Poland. For almost 30 years, an oak decline resulting from stress factors leading to a decrease of tree vitality in the long-term has been observed. The aim of the present study was to determine the proportion of leaves infected by the fungus Erysiphe alphitoides , the cause of powdery mildew, in post-flood oak stands situated in the Forest District Wołów (51°32’N, 16°62’E) as well as to evaluate effects of powdery mildew with respect to the oak decline. In order to record the powdery mildew incidence, we selected three trees in each of the ten investigated oak stands, and 200 leaves were collected from the upper part of the crowns. The percentage of infected leaves as well as the reduction of carbon assimilation capacity was assessed. Furthermore, we evaluated the average reduction of carbon assimilation capacity and the percentage of withering branch tips in 25 adjacent trees. Incidences of powdery mildew were observed in seven out of the ten stands. The maximum tree damage did not exceed 22% leaf infection and mean defoliation within the study areas ranged from 18% to 61.4%. Non-withering branch tips were observed in one post-flood area as well as in one area situated outside the flooded region. Within the remaining areas studied, the average proportion of withering branch tips ranged from 0.4% to 13.8%. Statistical analyses showed that differences between the investigated stands with regard to the rate of powdery mildew occurrence were not significant. Correlating the means, however, revealed a relationship between powdery mildew incidence and branch tip withering. This relationship is a possible indication of the ongoing oak dieback. No statistically significant relationship between tree defoliation and powdery mildew incidence was found. The lack of statistical significance, as observed here, implies that water stagnation within the investigated stands had no effect on Erysiphe alphitoides infection.